Polysaccharide-Coated Magnetic Nanoparticles for Imaging and Gene Therapy - Uthaman, Saji (Biomed Res Int, 2015)
Today, nanotechnology plays a vital role in biomedical applications, especially for the diagnosis and treatment of various diseases. Among the many different types of fabricated nanoparticles, magnetic metal oxide nanoparticles stand out as unique and useful tools for biomedical applications, because of their imaging characteristics and therapeutic properties such as drug and gene carriers. Polymer-coated magnetic particles are currently of particular interest to investigators in the fields of nanobiomedicine and fundamental biomaterials. Theranostic magnetic nanoparticles that are encapsulated or coated with polymers not only exhibit imaging properties in response to stimuli, but also can efficiently deliver various drugs and therapeutic genes. Even though a large number of polymer-coated magnetic nanoparticles have been fabricated over the last decade, most of these have only been used for imaging purposes. The focus of this review is on polysaccharide-coated magnetic nanoparticles used for imaging and gene delivery.